2008
DOI: 10.1186/1475-2875-7-232
|View full text |Cite
|
Sign up to set email alerts
|

Overuse of artemisinin-combination therapy in Mto wa Mbu (river of mosquitoes), an area misinterpreted as high endemic for malaria

Abstract: Background: Adequate malaria diagnosis and treatment remain major difficulties in rural subSaharan Africa. These issues deserve renewed attention in the light of first-line treatment with expensive artemisinin-combination therapy (ACT) and changing patterns of transmission intensity. This study describes diagnostic and treatment practices in Mto wa Mbu, an area that used to be hyperendemic for malaria, but where no recent assessments of transmission intensity have been conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 34 publications
(54 reference statements)
3
42
1
1
Order By: Relevance
“…Both situations result in extensive overuse of antimalarial drugs, especially in low transmission settings [19],[20].…”
Section: The Local Health Care Settingmentioning
confidence: 99%
“…Both situations result in extensive overuse of antimalarial drugs, especially in low transmission settings [19],[20].…”
Section: The Local Health Care Settingmentioning
confidence: 99%
“…Over-diagnosis (Elgayoum et al, 2009) and overtreatment of malaria (Chandler et al, 2008) may lead to missing other causes of febrile illnesses. This may result in overuse of antimalarial drugs (Mwanziva et al, 2008) and increases the chance of developing drug resistance (Maude et al, 2009;White, 2010). Furthermore, self-treatment (Nsimba & Rimoy, 2005;Hodel et al, 2009) and mistreatment of febrile illnesses in health facilities results into increasing hospitalization and deaths due to diseases other than malaria.…”
Section: Introductionmentioning
confidence: 99%
“…The inaccurate diagnosis of malaria is not peculiar to Nigeria. In Tanzania, Mwanziva et al [18] reported a very appalling case, where < 1% of the slides read by clinic microscopists as malaria positive were confirmed as positive by trained research scientists.…”
mentioning
confidence: 99%